Numerical Analysis of Seismic Performances of Post-Fire Scoria Aggregate Concrete Beam-Column Joints - Bin Cai; Wen-Li Hu; Feng Fu (Fire, 2021)
In order to analyze the post-fire seismic performances of scoria aggregate concrete (SAC) beam-column joints precisely and effectively, one finite element model (FEM) was developed to simulate the seismic behavior of SAC beam-column joints. The FEM consists of two sequential parts: firstly, the heat transfer analysis of the beam-column joints, and then the seismic analysis of the SAC joints by combining the temperature field distribution obtained from the heat transfer analysis with the mechanical properties of the SAC after fire, both of which were implemented in ABAQUS. In order to make the simulation results more accurate, spring elements were applied to simulate the bond–slip behavior with material degradation due to fire damage in the simulation of seismic analysis. Moreover, in order to validate the FEM, the seismic behavior of the natural aggregate concrete (NAC) beam-column joints after fire was simulated with the established FEM, and the simulation results were compared with the available test data. It is proved that the FEM we built was accurate and effective and provided efficient solutions for evaluating the seismic performance of post-fire beam-column joints so that the effects of various parameters, namely, fire time, longitudinal reinforcement ratio, and axial compression ratio on the seismic performance of SAC beam-column joints after fire were investigated in depth, which indicated the increase of axial compression ratio can improve the strength, initial stiffness, and energy dissipation capacity of SAC joints, while the increase of longitudinal reinforcement ratio can increase the strength and stiffness of SAC joints to a small extent, but too high reinforcement ratio will significantly weaken the energy dissipation capacity of SAC joints.